Study of central exclusive production in proton-proton collisions at s√=5.02s=5.02 and 13TeV; European Physical Journal C; Vol. 80, iss. 8 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer Th. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2020, 2020)
Title screen